(untitled) (REMUNOM, 2023)
According to the latest data from the Violence and Cities Surveillance system (Viva) of the Ministry of Health, sexual abuse is identified as the second most committed violence in the age group from 0 to 9 years old, behind only notifications of neglect and abandonment. According to data from the International Labor Organization (ILO), around 100,000 cases of sexual abuse and exploitation of children and adolescents occur in Brazil each year. But less than 20% of these cases come to the attention of those in charge of taking action. In this article I will discuss two serious problems faced by many children and adolescents: sexual exploitation and sexual abuse, and the challenges faced by the child and adolescent care and protection network in combating these types of violations. In addition to seeking to conceptualize and characterize this cruel form of violence, we will reflect on coping policies, accountability of exploiters and prevention, these being the main challenges in combating commercial sexual exploitation of children and adolescents.